FENOMENA MASIBIRI (KAWIN LARI) STUDI DI DESA BOBANEHENA KABUPATEN HALMAHERA BARAT - Fatah, Rahmat Abd; Kasim, Irma (JOURNAL OF ETHNIC DIVERSITY AND LOCAL WISDOM, 2019)
The eloping (masibiri) phenomenon often occurs in the Bobanehena community. Masibiri is escaping girl (future wife) from supervision her guardian as well as used as the first procession of her marriage. The method used in this study is descriptive qualitative. While the data collected in primary and secondary data. Data obtained from interviews, observation, and documentation. The results showed that the number of teenage masibiri marriages of Bobanehena Village from 2005-2017 was 27 people. The masibiriprocess carried out in four ways, such as; visiting jomodim (Mosque caretaker), the host reports to the village head, holds a meeting and reports to parents. The impact ofmasibiri is difficulties in the economy, the relationship not harmonious with both parents and the risk of litigation.